Memory Characteristics of the Ethnic Minority Vocational Students in Tay Nguyen and Southeast Provinces - Nguyễn Thị Lan (Journal of Technical Education Science, 2006)
Proper attachment of special importance to the private psychological characteristics and the specifi c characteristics in cultures of the ethnic groups is more and more required in competency-based-training and student-centered-training in multicultural and integrated contexts. Which psychological characteristics of the ethnic youths in Tay Nguyen and Southeast provinces need to be noticed in vocational training? This artcile is about to present some research outcomes on memory characteristics of the vocational ethnic students in Tay Nguyen and Southeast provinces analysed from the data of the research B2004-19-44TĐ.